Daya Hambat Perasan Bawang Dayak (Eleutherine Palmifolia (L.) Merr) Terhadap Pertumbuhan Bakteri Stapylococcus aureus Metode Difusi - Kamilla, Laila; Tumpuk, Sri; Salim, Maulidiyah (Jurnal Laboratorium Khatulistiwa, 2022)
Traditional medicine is an ingredient that can be derived from plants, animals, minerals, preparations of extract (galenic) or a mixture of these materials which have been used for generations for treatment. The use of medicinal plants as traditional medicine has many advantages. It is easy to obtain because the raw materials can be grown and mixed by yourself, so it is cheaper. People also consider traditional medicine to be safer than chemical drugs because the side effects are relatively smaller.One of the plants that have been used as traditional medicine is the Dayak onion. Dayak onion (Eleutherine americana L. Merr) is empirically used by local people in Kalimantan as a traditional medicinal plant. Dayak onions can be used as raw materials for medicine because they contain active compounds in the form of alkaloids, glycosides, flavonoids, phenolics, triterpenoids or steroids and anthraquinones which have been known as medicinal raw materials. Until now, the Dayak onion plant is used for the treatment of colon cancer, breast cancer, diabetes mellitus, hypertension, lowering cholesterol, stroke, stomach pain medication after childbirth and ulcer medicine.This study aims to determine the inhibition of Dayak onion (Eleutherine americana L. Merr) on the growth of Stapylococcus aureus bacteria by diffusion method. The research design was a quasi-experimental. The population of Dayak onion bulbs. As a sample of Dayak onion bulbs made in concentrations of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100%. With the formula of Randomized Block Design (RAK), 30 samples were obtained. Antimicrobial testing using the diffusion method.The results obtained were resistant at a concentration of 10% - 60% (inhibition zone < 9 mm) and a concentration of 70-90% intermediate (inhibition zone 10-11) and a concentration of 100% sensitive (inhibition zone > 12). After being analyzed statistically using the Kruskal-Wallis test, a significant asymp value was obtained. sig = 0.001 < 0.050. It was concluded that there was an effect of the juice of the Dayak onion (Eleutherine palmifolia (L.) Merr) in inhibiting the growth of Stapylococcus aureus bacteria.